DETEKSI HISTOLOGIK KESEMBUHAN LUKA PADA KULIT PASCA PEMBERIAN DAUN MENGKUDU (Morinda Citrofilia Linn) - Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2012)
A study to detect the microscopic structure of skin wound in mice (Mus musculus) aftertreatment with mengkudu leaves (Morinda citrifolia Linn.), by histological methods, hasbeen carried out. In this study were detected the level of wound healing every weeks. Thesamples were collected from skin with was given incision injury. The tissue samples werefixed, dehydrated and embedded in paraffin and 4 – 5 ?. sections. Harris-Haematoxilin-Eosin staining method, using to identified of histological structure.Microscopic analysiswas performed using a binocular light microscope (450X). The study showed that,histological structure of normaly skin we deteted in fourth weeks ware composed byepidermis, dermis and hipodermis tissue. We observed for the presence ofthe ephitelialsquomous complexs, hairfollicles, connective tissue with vein and arteriole and adiposetissue.
Keywords: Mus musculus; Morinda citrifolia Linn; structur microscopis; Haematoxilineosin; Epidermis; Dermis; Hipodermis